Economic Dislocation and Recovery in Lebanon - Martelino, Jose.; Eken, Sena.; Erbas, S.; Mazarei, Adnan (Washington, D.C. : International Monetary Fund, 1995)
This paper provides background information on the Lebanese economy, based on an analysis of the economic consequences of war, and discusses several issues that will be central to Lebanon's prospects for recovery.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet